Exosomes from Bone Marrow Mesenchymal Stem Cells with Overexpressed Nrf2 Inhibit Cardiac Fibrosis in Rats with Atrial Fibrillation. (15th March 2022) - Xu, Lijuan; Fan, Yingchao; Wu, Liting; Zhang, Cui; Chu, Min; Wang, Yuan; Zhuang, Wenfang
Abstract : Background . Even though nuclear factor-erythroid 2-related factor 2 (Nrf2) signaling has been associated with the pathogenesis of multiple heart conditions, data on roles of Nrf2 within atrial fibrillation (AF) still remain scant. The present investigation had the aim of analyzing Nrf2-overexpressing role/s upon bone mesenchymal stem cell- (BMSC-) derived exosomes in rats with AF. Methods . Exosomes were collected from control or Nrf2 lentivirus-transduced BMSCs and then injected into rats with AF through the tail vein. AF duration was observed using electrocardiography. Immunohistochemical staining was then employed for assessing Nrf2, HO-1, α -SMA, collagen I, or TGF- β 1 expression profiles within atrial myocardium tissues. Conversely, Masson staining was utilized to evaluate atrial fibrosis whereas apoptosis within myocardia was evaluated through TUNEL assays. In addition, TNF- α, IL-1 β, IL-4, or IL-10 serum expression was assessed through ELISA. Results . Results of the current study showed significant downregulation of Nrf2/HO-1 within AF rat myocardia. It was found that injection of the control or Lv-Nrf2 exosomes significantly alleviated and lowered AF timespans together with reducing cardiomyocyte apoptosis. Moreover, injection of Lv-Nrf2 exosomes essentially lowered AF-driven atrial fibrosis and also inhibited inflammatory responses in the rats with AF. Conclusion . Delivery of BMSC-derived exosomes using overexpressed Nrf2 inhibited AF-induced arrhythmias, myocardial fibrosis, apoptosis, and inflammation via Nrf2/HO-1 pathway triggering.